The Influence of Spirituality on Academic Engagement through Achievement Motivation and Resilience - Imron, Imron; Mawardi, Imam; Şen, Ayşenur (International Journal of Islamic Educational Psychology, 2023)
Academic involvement refers to the active participation of students in the learning environment. Several factors directly or indirectly influence students' academic involvement, including spirituality, achievement motivation, and resilience. This research aims to explore the impact of spirituality on academic involvement by examining its relationship with achievement motivation and resilience. The research adopted a quantitative correlational approach and considers three types of variables: independent variables, dependent variables, and intervening variables. The study involved 200 active students from the Islamic Religious Education Study Program at Universitas Muhammadiyah Magelang, who were selected using a lottery method. Data collection for this research was done through a questionnaire, and the analysis involved descriptive statistics and path analysis. The findings demonstrate a significant influence of spirituality on students' academic involvement through achievement motivation and resilience. Spirituality has an impact on both achievement motivation and resilience. Furthermore, the study revealed that achievement motivation and resilience shaped students' academic involvement. Spirituality positively affected academic involvement by promoting achievement motivation and resilience. Thus, students with strong spirituality tended to exhibit higher achievement motivation and resilience, positively contributing to their academic involvement.